2010
DOI: 10.1002/app.32567
|View full text |Cite
|
Sign up to set email alerts
|

Properties improvement of PMMA using nano TiO2

Abstract: TiO 2 nanofillers (5 nm, 0-15% weight) have been introduced in the PMMA matrix using a twin screw extruder to increase the performance of PMMA. The twin screw extrusion process is optimized to disperse the particles into PMMA. Nanofiller infusion improves the thermal, mechanical, and UV absorption properties of PMMA. TiO 2 -PMMA nanocomposites exhibit the increase in tensile modulus (90%), decomposition temperature (31%), dimension stability ($ 60%) and UV absorption ($ 410%). Properties of the nanoTiO 2 -PMMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 23 publications
0
81
0
Order By: Relevance
“…19 However, the concentration of nanoparticles in silicone elastomers at 4% and 6% exhibited a certain degree of agglomeration, in which the molecular chains were fixed more firmly around the nanoparticles, weakening the interaction with the silicone elastomer. 20 Kulik et al 21 and Chatterjee 22 suggested that the high modulus characteristics of nanoparticles can decrease the elastic modulus of the filling material. However, it is imperative that facial epitheses used for the repair of soft tissue defects retain elasticity.…”
Section: Tensile and Tear Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…19 However, the concentration of nanoparticles in silicone elastomers at 4% and 6% exhibited a certain degree of agglomeration, in which the molecular chains were fixed more firmly around the nanoparticles, weakening the interaction with the silicone elastomer. 20 Kulik et al 21 and Chatterjee 22 suggested that the high modulus characteristics of nanoparticles can decrease the elastic modulus of the filling material. However, it is imperative that facial epitheses used for the repair of soft tissue defects retain elasticity.…”
Section: Tensile and Tear Propertiesmentioning
confidence: 98%
“…38 Similarly, the duration of UV ageing engenders a proportional increase in hydrolytic reactions and accelerates the scission of the main chain in the elastomer. 34,22,35 It has been found that nano-TiO 2 has a strong ability to resist UV rays. Indeed, the nanoparticles can not only absorb, but also reflect and scatter UV rays due to their refractive index and optical activity.…”
Section: Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly (methyl methacrylate) (PMMA) is an excellent host for functional inorganic particles; in particular, the introduction of TiO 2 into a PMMA matrix received much attention due to improvements in the glass transition and thermal stability of the composites [23][24][25], but a little attention has been addressed to the applications of the PMMA-TiO 2 nanocomposites for water purification. We believe this can play a major role in water purification issues.…”
Section: Introductionmentioning
confidence: 99%
“…Both titanium and silicon dioxide nanosized particles have been widely used to extend the functional characteristics of polymer composites . For example, the embedding of titanium dioxide (TiO 2 ) nanoparticles into thermosetting polymers and elastomers results in enhancements in their thermal resistance, stiffness and toughness, thermal conductivity, tensile properties, impact strength, and fracture toughness . It is remarkable that the aforementioned improvements manifest themselves at low filler contents (≤5 wt %) and are related to the stabilization of the polymer's inner structure because of the binding of macromolecular chains to the superficial centers of the particles …”
Section: Introductionmentioning
confidence: 99%